The Role of Job Satisfaction on Turnover Intention with Employee Engagement as a Mediating Variable - Lubis, Rizky Amelia; Lubis, Zulkarnain; Patisina, Patisina (Journal of Educational, Health and Community Psychology, 2024)
Dissatisfaction often arises from factors related to workload, with heavy workloads driving employees to consider leaving for other companies. However, highly engaged employees are more likely to contribute positively through ideas and actions, and are more likely to stay with the organization longer. This study investigates the impact of job satisfaction on turnover intention, with employee engagement serving as a mediating variable. A quantitative approach was employed, surveying 315 employees at Company X in Tanjung Morawa, all with 2 to 5 years of service. The results of the mediation analysis using SEM-PLS reveal that employee engagement significantly mediates the relationship between job satisfaction and turnover intention. To reduce turnover intention, organizations should prioritize enhancing employee engagement by improving factors that contribute to job satisfaction.